Pelanggaran prinsip kesantunan tindak tutur dalam iklan berbahasa jawa di radio RRI Semarang - Amirulchaq, Muhammad Arif; Sunarya, Sunarya; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
The language used in Semarang radio advertisements has its own characteristics, such as the use of Javanese dialect which sometimes sounds harsh. Many members of the public consider advertisements to be disrespectful, as can be seen from the language used in many advertisements. Obviously, this cannot be separated from the culture that surrounds it, because politeness and modesty are a reflection of society. It is hoped that the language used in Semarang radio advertisements will not change the intended meaning. The aim of this research is to describe the types of speech acts and violations of politeness principles contained in Javanese language advertisements on RRI Radio Semarang. This research is a qualitative research. The data source in this research is Javanese language advertisements on RRI Radio Semarang, while the data in this study is in the form of words and sentences in Javanese language advertisements on radio. The data collection technique carried out in this research was the SBLC technique (skilled free-involved listening technique). In analyzing the data, researchers also used the pragmatic matching method. The results of this research are that the types of speech acts in Javanese language advertisements on RRI Radio Semarang include assertive, directive, commissive, expressive speech acts and declarations as well as violations of politeness principles found in Javanese language advertisements on RRI Radio Semarang which occur in four maxims, namely the maxim of wisdom, generosity, praise and humility.